Trust evaluation model based on improved D-S evidence theory - Lin ZHANG; Jing-wen LIU; Ru-chuan WANG; Hai-yan WANG (Tongxin xuebao)
The existing trust evidence models cannot deal with malicious attacks in the distributed net quickly and effectively, and are lack of a trust normalization method that can measure relationship described by a triple set, so a trust model based on the improved D-S evidence theory was proposed. On this basis, basic trust value function based on continuous sequences and trust evaluation method based on evaluation function were also proposed to inhibit malicious nodes in a higher speed, and to enable the prediction results to be closer to the fact. Analysis and simulation show that this model has better effectiveness and robustness to deal th the aggregating trust attack, and trust evaluation method has better reasonableness and accuracy.